Efficacy of Multiple Isocentric Volumetric Modulated Arc Therapy (VMAT) for Treatment of Bilateral Breast Carcinoma - Bali Rathore, Vikram; Kumar Chandrakar, Pradeep; Choudhary, Vivek; Kumar Azad, Surendra; Kerketta, Manjula (International Journal of Medical Research and Review, 2015)
Treating bilateral breast cancer with radiotherapy by conventional techniques is difficult because it requires multiple field settings from different orientations resulting in hot and cold spots at field junctions. Planning with Volumetric Modulated Arc therapy gives uniformity in dose distribution, minimizing hot and cold spots resulting in high doses to target and minimum dose to normal tissues. Volumetric Modulated Arc Therapy (VMAT) has been done on a patient with bilateral breast Cancer with two isocentres and dual half arcs in each isocentre. Mean dose achieved to PTV (Planning Target Volume) was 50Gy. The values of Conformity index (CI) and Homogeneity index (HI) were found to be 1.2 and 1.9 respectively. Maximum doses to lung, liver and heart were found in the region close proximity to the target. VMAT is found to be better technique for treating bilateral breast cancer. Post radiotherapy follow up at two years showed complete control of both primaries without any systemic recurrence and significant side effects.